2020
DOI: 10.1155/2020/8026547
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Plasma Amino Acid Levels in Preterm Infants and Their Potential Correlation with Retinopathy of Prematurity

Abstract: Aim. The aim of this study is to ascertain whether the level of circulating amino acids (aa) is associated with retinopathy of prematurity (ROP). Methods. This is a randomized controlled study of 55 infants born at gestational age (GA) ≤32 weeks or birth weight (BW) ≤1500 grams. Serum samples were obtained from two groups: Group A comprised of 26 preterm infants with ROP and Group B comprised of 29 preterm infants without ROP. Plasma aa levels were analyzed using liquid chromatography with tandem mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The pathogenesis of ROP as well as its comorbidities inevitably result in profound changes in metabolism and nutrition. Particularly, previous studies have indicated the importance of amino acids in ROP pathogenesis [4,5]. Better nutrition, especially supplementation of amino acids is essential for the synthesis of growth factors like insulin-like growth factor-1 (IGF-1), which plays a crucial role in the Ivyspring International Publisher progress of ROP [6].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of ROP as well as its comorbidities inevitably result in profound changes in metabolism and nutrition. Particularly, previous studies have indicated the importance of amino acids in ROP pathogenesis [4,5]. Better nutrition, especially supplementation of amino acids is essential for the synthesis of growth factors like insulin-like growth factor-1 (IGF-1), which plays a crucial role in the Ivyspring International Publisher progress of ROP [6].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the potential as biomarkers, different amino acids have different characteristics, leading to various clinical applications. Glutamine and arginine tend to increase in peripheral blood samples from DR, AMD, and ROP patients according to the analysis of metabolomics [17][18][19][20][21]23,[25][26][27][28][29]43,45,52,55,56,58], which makes it possible and reasonable for glutamine and arginine to be the biomarkers used in early diagnosis of retinopathy. In addition, the level of alanine rises in DR patients in intraocular fluids, blood samples, and even in CSF and urine while not showing clear tendency in AMD and ROP [19,22,27,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…However, the group with worsened ROP also had a significantly lower mean gestation age, which may have affected the outcome. 18 Additionally, a case-control study further demonstrated elevated citrulline and aminoadipic acid in neonates with ROP. 19 Contrary to these findings, supplementation using a dipeptide of glutamine and arginine inhibited vascular endothelial growth factor expression and, therefore, neovascularisation in oxygen-induced retinopathy murine models.…”
Section: Parenteral and Enteral Nutritionmentioning
confidence: 98%